High diversity of lysis‐resistant cells upon the application of targeted physical and chemical lysis to environmental samples originating from three different water bodies. Issue 5 (19th May 2022) - Junier, Thomas; Paul, Christophe; Corona Ramírez, Andrea; Filippidou, Sevasti; Fatton, Mathilda; Lehmann, Anaël; Chain, Patrick S.; Ariztegui, Daniel; Vennemann, Torsten; Viollier, Patrick H.; Junier, Pilar
Abstract: In most habitats, fluctuating environmental conditions create periods of compromised survival for metabolically active organisms. In response, various survival strategies have evolved, including the formation of resilient resting cells. We assessed the biodiversity of the lysis‐resistant bacteria in three different environments by applying a harsh physicochemical treatment to the samples. The bacterial diversity of the lysis‐resistant fraction was compared with the bacterial diversity from the same environmental samples without the application of the enrichment method. As expected, in the lysis‐resistant fraction, a significantly higher relative abundance of endospore‐forming Firmicutes (for instance, Bacillus, Clostridium and Paenisporosarcina ) was observed in comparison with the untreated samples. However, genera from which the existence of a resistant cell form is not yet reported were also highly enriched in comparison with the untreated samples. Our results suggest a more diversified repertoire of bacterial resistant cellular structures than previously thought. Abstract : In this article we investigate the diversity of lysis‐resistant cells in bacteria and show that many bacteria not previously known for lysis‐resistance are found in the environment.